Genre and Autonomy in Cultural Production: The case of travel guidebook production - Ana Alačovska (Copenhagen Business School (CBS), 2013)
This thesis focuses on the production of travel guidebooks. Its aim is to explore the mutual coconstruction and entanglement of genres, producers and institutions in cultural production and cultural work. It also examines how authorial and institutional, professional and industrial selfreflexivity exists in and through ambiguous and shifting interrelations with genres and their poetics. To this end, it develops a preliminary theoretical framework for a comprehensive exploration of the complex dynamics of cultural production that is attentive to the cultural objects themselves: here, a down-market, `uninventive' and `heteronomous' genre known as the travel guide(book). The thesis argues that the specificity of the genre is continually contextualized and re-contextualized, qualified and re-qualified, commodified and rendered autonomous, in the daily, local, and intimate practices of guide-making. The argument presented is that the genre is not merely a backdrop for creative agency or a predetermined set of rules, but a complex entity – spatially and temporally dispersed – that affords autonomous opportunities for various modes of action, self-definition, and self-interpretation. Thus, genres are active elements or animating forces of cultural production, rather than merely outcomes of industrial dynamics. What arises from the empirical material is that cultural producers experience `autonomy' in and through the notion of genre which itself is fuzzy, vague, tacit, implicit and often non-formalized. Nonetheless, it is obdurately present in a spectrum of strategies, rhetoric, a sense of responsibility, expertise and professionalism applied by such producers in order to explain, define and justify their practical decisions and evaluations. The first three chapters explore perceived limitations of sociological, anthropological and sociocultural paradigms of cultural production. They also indicate some potential areas for crossfertilization with genre theory, which has conceptualized the notion of genre as social action, cognitive action-schemata, and institutions that mediate between industry, producers, and audiences. The last four chapters follow and trace interpenetrating and interlocking relations between genres and institutions firstly, as they mutually and historically co-produce each other in industrial practice; secondly, as entangled in individual and professional auto-biographies with reference to the genre and its adjacent markets; and third, as embedded in actual production practices - how guidebook producers make use of and interact with the editorial brief (or institutionalized and contractually binding genre specificity) and independent genre trajectories (autonomous logic), while making daily evaluations of their work and their own professional selfreflexivity.
hdl:10398/8703
Keywords: 650